2019
DOI: 10.2106/jbjs.rvw.18.00129
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Avoid Osteonecrosis in Unstable Slipped Capital Femoral Epiphysis

Abstract: Osteonecrosis of the femoral epiphysis following slipped capital femoral epiphysis (SCFE) causes substantial patient morbidity.» The etiology of osteonecrosis following SCFE is multifactorial, and multiple treatment strategies, including techniques of epiphyseal reduction, capsulotomy, and timing of surgical intervention, that are intended to reduce this risk have been utilized. » At the present time, because of conflicting data and the lack of high-level evidence, there are a paucity of data to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
0
10
1
Order By: Relevance
“…Number of implants also plays a role in fixation stability, with several studies showing modest improvements in stability when using multiple implants, especially for intrinsically less stable severe slips requiring multiple fixation points. [18][19][20][21] However, some authors argue that adding implants increases intraarticular penetration and improper placement, elevating the risk for serious complications (eg, AVN, chondrolysis). 22 While several clinical studies have demonstrated increased risk of AVN with multiple implants, others report similar AVN rates in single-implant and multiple-implant fixation constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Number of implants also plays a role in fixation stability, with several studies showing modest improvements in stability when using multiple implants, especially for intrinsically less stable severe slips requiring multiple fixation points. [18][19][20][21] However, some authors argue that adding implants increases intraarticular penetration and improper placement, elevating the risk for serious complications (eg, AVN, chondrolysis). 22 While several clinical studies have demonstrated increased risk of AVN with multiple implants, others report similar AVN rates in single-implant and multiple-implant fixation constructs.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the current literature, the best treatment for stable SCFE is in situ pinning with a single screw, performed regardless of the timing of presentation [ 36 ]. The unstable SCFE is related to a higher risk of osteonecrosis (20–50% of cases) [ 37 39 ], but the proper treatment and the timing associated with the lowest risk of AVN are still debated [ 11 , 36 ].. The technique described by Parsch and colleagues (open capsulotomy and partial reduction) seems to be the most promising, reporting a low rate of AVN [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The technique described by Parsch and colleagues (open capsulotomy and partial reduction) seems to be the most promising, reporting a low rate of AVN [ 40 ]. Moreover, the modified Dunn procedure historically reported satisfactory outcomes with a low rate of necrosis, but it is widely influenced by the surgeon’s technique and skills [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intraoperative assessment of femoral head perfusion is becoming increasingly common when treating SCFEs [ 31 , 32 ]. Many studies have now published results suggesting that this may be a more accurate and easier way to predict the development of AVN rather than previously described methods such as MRI, bone scan or angiography [ 14 , 19 ].…”
Section: Discussionmentioning
confidence: 99%